The Influence of Emulsifier on Rheological and Sensory Properties of Cosmetic Lotions - Tereza Moravkova; Petr Filip (Advances in Materials Science and Engineering)
Three body lotions (water-in-oil type) differing only in the emulsifier content were subjected to rheological measurements and sensory analysis with the aim to obtain coupling between the selected rheological characteristics and sensory factors. Both methods proved different behaviour of the samples caused by the difference in the emulsifying compound. To detect the relations between rheological (application of the power law model) and sensory variables, the four most important characteristics from sensory assessment (ease of pouring from the bottle, ease of spreading on a palm, thickness, and ease of spreading on back of hand) were selected. A close coupling (and hence mutual substitution) was found between consistency parameter k and thickness, k and the ease of pouring from the bottle, and also k and the mean droplet size.